TI_GERICHTE 11.2019.135 vom 7. September 2020 , Dichiarazione di scomparsa in caso di persona "da lungo tempo assente" - TI Tribunale d'appello (2020)
Dichiarazione di scomparsa in caso di persona "da lungo tempo assente"